PENINGKATAN PENCAPAIAN BELAJAR MATEMATIKA MENGGUNAKAN STRATEGI TANDUR - Joko Purwanto; Kusno Kusno (PAEDAGOGIA, 2009)
This research aims at revealing learning achievement using Tandur Strategy. The research made use of descriptive and inferential analyses using ANAKOVA. The results of the research showed that: (1) students who were taught using Tandur strategy on the topic of Linier Program have finished classical comprehension, while students who were taught conventionally have not finished classical comprehension; (2) on the base of Inferential Statistic Analyses using ANAKOVA, the students who were taught usingTandurStrategywasdifferentsignificantlyfromthestudentswhoweretaughtusing conventional learning model. These analyses revealed that the result of study of the students who followed Linier Program Learning using Tandur Strategy were better than thosewhojoinedLinierProgramLearningusingconventionalmodelinMathematics.